Effect of OPG-supplemented diet on immune and stress responses and attenuation of LPS-induced damage in the liver of carp (Cyprinus carpio haematopterus) - Haicheng Yin; Zhixiang Yang (Boletim do Instituto de Pesca)
Effects of oxidized peptidoglycan (OPG) on immune and stress responses and lipopolysaccharide (LPS)-induced damage in the liver of carp were investigated in this study. Four hundred carps (Cyprinus carpio haematopterus) were fed with five experimental diets supplemented with 0, 100, 200, 400, and 800 mg kg-1 OPG for 28 days. Each group had four replicates and 20 fish per replication. LPS challenge (injection of 40 mg kg-1 saline or LPS) occurred at day 29. The supplementation with OPG linearly increased (p<0.05) plasma total protein, immunoglobulin M (IgM), complement 4 (C4), cortisol, and lactate on day 14. Dietary supplementation with OPG linearly increased (p<0.05) plasma and complement 3 (C3); quadratically improved (p<0.05) alkaline phosphatase (ALP) and lysozyme (LYS) activities; linearly increased hepatic superoxide dismutase (SOD) and catalase (CAT) activities; increased malondialdehyde (MDA) contents; and improved (p<0.05) hepatic anti-superoxide anion (ASA) and anti-hydroxy radical (AHR) contents on days 14 and 28. Dietary OPG significantly prevented the increase of interleukin 1β (IL-1β), interleukin 6 (IL-6), and tumor necrosis factor α (TNF-α) by inhibiting the excessive activation of TLR2-Myd88 signaling pathway; downregulating TLR2, Myd88, and NF-κB p65; and upregulating nuclear factor erythroid-2-related factor 2 (Nrf2) and Keap1 mRNA expression (p<0.05). Therefore, this study indicated that dietary OPG improves the plasma immune response, regulates the hepatic antioxidant status, and attenuates LPS-induced negative effects in the carp at the optimal dose of 400 mg kg-1.